Study of Grain Size Parameters of Ras Ben Hane Beach Sediments -Latakia - Ghadeer , Samer; Sakalli, Nesrin (Latakia University Journal -Basic Sciences Series, 2018)
The study of textural characteristics of marine sediments is very important to understand the evolution and distribution of coastal deposits, the hydrodynamic conditions of the depositional environments, and seasonal changes along the coasts, by collecting samples during seasonal periods. Due to the lake of sach studies in our coast, aset of 14 samples has been collected from superficial sediments of Ras Ben Hane beache during the beriod that range between 10/2015 and 6/2016. the grain size parameters (Mean, Standarddiviation, Skewness, and Kurtosis) showed that the grains are coarse to very coarse in their size, moderately to poorly sorted, coarse to strongly coarse skewed, and mesokurtic to platykurtic. Based on the CM patterns, the samples fall in rolling fields, while their morphological study showed that most of grains are subrounded.these parameters confirm that the sediments were deposited under high energy conditions, as the coarse and very coarse grains need high energy to more by rolling on the sea bed. while the subrounded shape of the grains indicates that the grains are transported for along distance befor they settels down in their site of deposition.